Analysis of cardiovascular dynamics in pulmonary hypertensive C57BL6/J mice - Tewari, Shivendra; Bugenhagen, Scott; Wang, Zhijie; Schreier, David; Carlson, Brian; Chesler, Naomi; Beard, Daniel (Frontiers in Physiology, 2013)
A computer model was used to analyze data on cardiac and vascular mechanics from C57BL6/J mice exposed to 0 (n = 4), 14 (n = 6), 21 (n = 8) and 28 (n = 7) days of chronic hypoxia and treatment with the VEGF receptor inhibitor SUGEN (HySu) to induce pulmonary hypertension. Data on right ventricular pressure and volume, and systemic arterial pressure obtained before, during, and after inferior vena cava occlusion were analyzed using a mathematical model of realistic ventricular mechanics coupled with a simple model of the pulmonary and systemic vascular systems. The model invokes a total of 26 adjustable parameters, which were estimated based on least-squares fitting of the data. Of the 26 adjustable parameters, 14 were set to globally constant values for the entire data set. It was necessary to adjust the remaining 12 parameters to match data from all experimental groups. Of these 12 individually adjusted parameters, three parameters representing pulmonary vascular resistance, pulmonary arterial elastance, and pulmonary arterial narrowing were found to significantly change in HySu-induced remodeling. Model analysis shows a monotonic change in these parameters as disease progressed, with approximately 130% increase in pulmonary resistance, 70% decrease in unstressed pulmonary arterial volume, and 110% increase in pulmonary elastance in the 28-day group compared to the control group. These changes are consistent with prior experimental measurements. Furthermore, the 28-day data could be explained only after increasing the passive elastance of the right free wall compared to the value used for the other data sets, which is likely a consequence of the increased RV collagen accumulation found experimentally. These findings may indicate a compensatory remodeling followed by pathological remodeling of the right ventricle in HySu-induced pulmonary hypertension.